Cofactor-Independent Antiphospholipid Antibodies: Implications for Pathogenesis, Diagnosis, and Treatment of Antiphospholipid Syndrome - Lackner, Karl J.; Müller-Calleja, Nadine (Hämostaseologie, 2019)
The antiphospholipid syndrome (APS) has occupied haemostaseologists, rheumatologists and obstetricians since its initial description 35 years ago. Its name has been coined because of the antibodies against phospholipids which were the common property of affected patients. In particular, the pathogenesis of APS has been intensively studied after the early discovery that it was possible to induce the clinical manifestations in animals by transfer of antiphospholipid antibodies (aPL). In recent years, it has become clear that aPL are not only structurally heterogeneous but also have different pathogenic properties. This review will focus on the relevance of antigenic specificity of aPL in terms of pathogenesis, diagnosis, and perhaps treatment of APS.
Keywords: antiphospholipid antibodies; antiphospholipid syndrome; β2-glycoprotein I; lupus anticoagulant